EVALUATION OF REPRODUCTIVE PERFORMANCE AND MILK PRODUCTION POTENTIALS OF LOCAL COWS UNDER FARMER’S MANAGEMENT IN AND AROUND JINKA TOWN IN SOUTH OMO ZONE, SOUTHERN ETHIOPIA - WOLDE, BOGALE; KEJELA, YONAS; SIRAG, HUSSIEN; DEBEBE, SOLOMON (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
The study was conducted in and around Jinka Town to investigate the reproductive and productive performances of local cows under the farmer’s management. Six kebeles were selected from in and around Jinka town by simple random sampling technique. One-hundred and twenty households (60 from each) were used for the household survey. Data were collected through semi-structured questionnaires, focus group discussions, and secondary sources. The data were analyzed by using the SPSS version 20 and the mean comparison was made by LSD. An average age at first mating for male cattle was significantly (p<0.05) higher in Jinka town than around it. Average number of calves produced in lifetime was significantly higher around kebeles than in Jinka town. The overall mean±SE age at sexual maturity for both female and male cattle was 3.75±.05 and 3.38±.05 year, respectively. The overall mean±SE milk production per cow per was 1.28±0.35 liter per a day. Lactation milk yield per cow was significantly higher in town than around kebeles of Jinka town. During focus discussion and interview, the most breeding practices problems that hinder herd productivity were long calving interval, delayed age at first calving, postpartum anoestrous, seasonal fluctuation, the genetic makeup of animals, inadequate AI services and lack of skilled manpower. Generally, milk production in and around Jinka town is of subsistence type. On station investigation of production and reproduction performances of the local cattle is recommended through correlation studies and regular monitoring of the population to select the best animals, pasture improvement, and introducting technology that will enhance nutritive value of crop residue and dry season feed resources are needed.